2021
DOI: 10.1371/journal.pone.0252711
|View full text |Cite
|
Sign up to set email alerts
|

The Goto Kakizaki rat: Impact of age upon changes in cardiac and renal structure, function

Abstract: Background Patients with diabetes are at a high risk for developing cardiac dysfunction in the absence of coronary artery disease or hypertension, a condition known as diabetic cardiomyopathy. Contributing to heart failure is the presence of diabetic kidney disease. The Goto-Kakizaki (GK) rat is a non-obese, non-hypertensive model of type 2 diabetes that, like humans, shares a susceptibility locus on chromosome 10. Herein, we perform a detailed analysis of cardio-renal remodeling and response to renin angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The extracted biological pathways from the gene expression profiles confirmed a downregulated pattern of most involved genes in the GK rats. The most prominent gene pathway was diabetic cardiomyopathy, fitting previous reports of ventricular hypertrophy, impaired diastolic function, and cardiomyopathy in GK rats ( 66 , 67 ) that may be mediated by CRP ( 68 ). This peripheral gene expression profile contrasts sharply with the inflammatory profile of the GK rat pancreatic islets, where similar to diabetic human islets ( 69 ), we consistently show increased pro-inflammatory cytokine levels, associated with increased pro-inflammatory immune cell numbers around and within the pancreatic islets ( 13 , 14 , 35 ).…”
Section: Discussionsupporting
confidence: 84%
“…The extracted biological pathways from the gene expression profiles confirmed a downregulated pattern of most involved genes in the GK rats. The most prominent gene pathway was diabetic cardiomyopathy, fitting previous reports of ventricular hypertrophy, impaired diastolic function, and cardiomyopathy in GK rats ( 66 , 67 ) that may be mediated by CRP ( 68 ). This peripheral gene expression profile contrasts sharply with the inflammatory profile of the GK rat pancreatic islets, where similar to diabetic human islets ( 69 ), we consistently show increased pro-inflammatory cytokine levels, associated with increased pro-inflammatory immune cell numbers around and within the pancreatic islets ( 13 , 14 , 35 ).…”
Section: Discussionsupporting
confidence: 84%
“…More extensive phenotyping of these rats has shown that by 48 weeks of age these animals exhibit concentric LV hypertrophy associated with adverse myocardial remodeling, pulmonary congestion, and diastolic dysfunction. 106 Whereas their LVEF at 48 weeks is within the normal range for rats in general, it is important to note that LVEF significantly declines from 24 to 48 weeks in these animals, which is not entirely consistent with clinical HFpEF.…”
Section: Goto Kakizaki Ratmentioning
confidence: 81%
“…Female GK rats have reduced myocardial blood flow and contractility at the age of 8 to 13 mo, as assessed by perfusion and cine MRI ( 167 ). Ultrasound echocardiography studies have demonstrated that male GK rats have preserved systolic but reduced diastolic function at 6 to 7 mo of age, indicative of a diabetic cardiomyopathy phenotype ( 168 , 169 ), whereas systolic function declines at 12 mo of age ( 170 ). Other studies show preserved basal contractility in isolated perfused hearts ( 171 ) and in isolated ventricular myocytes ( 172 ).…”
Section: In Vivo Models Of Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%